Reference Values of Pulse Wave Velocity in Healthy People from an Urban and Rural Argentinean Population - Alejandro Díaz; Cintia Galli; Matías Tringler; Agustín Ramírez; Edmundo Ignacio Cabrera Fischer (International Journal of Hypertension)
In medical practice the reference values of arterial stiffness came from multicenter registries obtained in Asia, USA, Australia and Europe. Pulse wave velocity (PWV) is the gold standard method for arterial stiffness quantification; however, in South America, there are few population-based studies. In this research PWV was measured in healthy asymptomatic and normotensive subjects without history of hypertension in first-degree relatives. Normal PWV and the 95% confidence intervals values were obtained in 780 subjects (39.8 ± 18.5 years) divided into 7 age groups (10–98 years). The mean PWV found was 6.84 m/s ± 1.65. PWV increases linearly with aging with a high degree of correlation (r2=0.61; P<0.05) with low dispersion in younger subjects. PWV progressively increases 6–8% with each decade of life; this tendency is more pronounced after 50 years. A significant increase of PWV over 50 years was demonstrated. This is the first population-based study from urban and rural people of Argentina that provides normal values of the PWV in healthy, normotensive subjects without family history of hypertension. Moreover, the age dependence of PWV values was confirmed.